Foreign Shareholdings Impact on Credit Risks of Acquired Local Bank in Indonesia - Aswin Rivai, Rina Indiastuti, Adhy Firdaus (International Journal of Advanced Science and Technology, 2020)
The research investigate the impact of foreign shareholding originated from developed and developing countries on the credit risks of acquired local banks in Indonesia during 2007-2017 by including Corporate Governance as a moderating variable. This research used data of 29 commercial banks acquired by foreign shareholders. A panel regression model with generalized least square is applied to examine the effects of percentages of foreign shareholdings on credit risks of the acquired local banks. This research concludes that foreign shareholdings decrease credit risks of acquired local banks only if the foreign shareholders is majority shareholders and originated from developed countries. The minority shareholders from developing countries increase credit risks. Furthermore, increase in the size of the board of directors has no impacts on credit risks. Finally, the presence of foreign director originated from more developed countries strengthening the effect of percentage of foreign shareholdings on decreasing the credit risks of the acquired local banks. Overall, the originality of this research is the findings that both the percentages of foreign shareholdings and its country of origin are two combined factors that cannot be separated in affecting credit risks of its acquired local bank and the fact of significant positive moderating effect of foreign director originated from developed countries. As policy consideration, monetary authority need to perform strict due diligence on prospective foreign shareholders specifically originated from developing countries, to encourage investing by shareholders from more developed countries and advise banks to maintain the existence of foreign director.